A Fault-Tolerant Architecture for Supporting Large Scale Digital Libraries - Mariella Di Giacomo; Mark Martinez; Jeff Scott; Rick Luce (Issues in Science and Technology Librarianship)
At the Research Library of Los Alamos National Laboratory (LANL), we have developed an affordable multi-terabyte redundant RAID system -- running on Linux -- that addresses the needs of a constantly growing demand for electronic journals, conferences and standards. Although there are several practical issues associated with systems supporting electronic content -- such as acquisition, archiving, access and cataloging -- this paper will focus on archiving and providing access to electronic journals. This article explains the design and development of a scalable, fault-tolerant and affordable system, presents an overview of the architecture, summarizes the problems and architectural issues encountered, and describes the technical solutions adopted.